Klotho‐mediated targeting of CCL2 suppresses the induction of colorectal cancer progression by stromal cell senescent microenvironments. Issue 11 (6th October 2019) - Liu, Yangyang; Pan, Jie; Pan, Xia; Wu, Lunpo; Bian, Jun; Lin, Zhenghua; Xue, Meng; Su, Tingting; Lai, Sanchuan; Chen, Fei; Ge, Qiwei; Chen, Luyi; et al.
Abstract : Senescent microenvironments play an important role in tumor progression. Here, we report that doxorubicin (DOX)‐pretreated or replicative senescent stromal cells (WI‐38 and HUVEC) promote colorectal cancer (CRC) cell growth and invasion in vitro and in vivo . These pro‐tumorigenic effects were attenuated by exogenous administration of Klotho, an anti‐aging factor. We subsequently identified several senescence‐associated secretory phenotype (SASP)‐associated genes, including CCL2, which were significantly upregulated in both types of senescent stromal cells during replication and DNA damage‐induced senescence. Importantly, we found that the secretion of CCL2 by senescent stromal cells was significantly higher than that seen in nonsenescent cells or in senescent cells pretreated with Klotho. Notably, CCL2 was found to accelerate CRC cell proliferation and invasion, while this effect could be blocked by administration of a specific CCR2 antagonist. We further show that Klotho can suppress NF‐κB activation during DOX‐induced senescence and thus block CCL2 transcription. Low expression of Klotho, or high expression of CCL2 in patient tumor tissues, correlated with poor overall survival of CRC patients. Collectively, our findings suggest that senescent stromal cells are linked to progression of CRC. Klotho can suppress the senescent stromal cell‐associated triggering of CRC progression by inhibiting the expression of SASP factors including CCL2. The identification of key SASP factors such as CCL2 may provide potential therapeutic targets for improving CRC therapy. Abstract : The senescent microenvironment plays an important role in tumor progression. This study reports that senescent stromal cells can promote colorectal cancer progression through activation of senescence‐associated secretory phenotype‐associated genes including CCL2. Klotho, an anti‐aging factor, was shown to suppress NF‐κB activation and subsequently inhibit CCL2 secretion to attenuate the senescent stromal cell‐triggering pro‐tumorigenic effects.